A Study of Parallelism of the Occlusal Plane and AlaTragus Line - Katayoun Sad; Makan Sadr (Tabriz University of Medical Sciences, 2009)
Background and aims. Orientation of the occlusal plane is one of the most important clinical procedures in prosthodontic rehabilitation of edentulous patients. The aim of this study was to define the best posterior reference point of alatragus line for orientation of occlusal plane for complete denture fabrication. Materials and methods. Fifty-three dental students (27 females and 26 males) with complete natural dentition and Angel's Class I occlusal relationship were selected. The subjects were photographed in natural head position while clenching on a Fox plane. After tracing the photographs, the angles between the following lines were measured: the occlusal plane (Fox plane) and the superior border of ala-tragus, the occlusal plane (Fox plane) and the middle of ala-tragus as well as the occlusal plane (Fox plane) and the inferior border of ala-tragus. Descriptive statistics, one sample t-test and independent ttest were used. P value less than 0.05 was considered significant. Results. There was no parallelism between the occlusal plane and ala-tragus line with three different posterior ends and one sample t-test showed that the angles between them were significantly different from zero (P < 0.05). However, the superior border of ala-tragus line had the lowest mean angle, 1.80° (3.12) and was almost parallel to the occlusal plane. Conclusion. The superior border of the tragus is suggested as the posterior reference for ala-tragus line